A cross-sectional study on socio-demographic profile and associated risk factors of chronic kidney disease patients in a tertiary care hospital of Andhra Pradesh - Kanyari, S. Suneeti; Panda, Sangram; Shruthi, Peethala (International Journal Of Community Medicine And Public Health, 2020)
Background: Chronic kidney disease (CKD) is a global problem, and its prevalence is increasing dramatically. In chronic kidney disease (CKD) there is progressive loss in kidney function over a period of time. The objectives of this study were to study the socio-demographic characteristics and associated risk factors in CKD patients so as to suggest preventive measures for CKD and its long term health consequences. Methods: A cross-sectional study was conducted at MIMS Medical College, Vizianagaram, Andhra Pradesh among 194 confirmed CKD patients. A pre-tested, pre-designed questionnaire was used for collecting data on socio-demographic characteristics like age, education, occupation, residence, income etc. After completion of the questionnaire, the patients were subjected to anthropometric measurements, abdominal ultrasonography and their laboratory reports were assessed. Results: Out of 194 CKD patients, 148 were males and 46 were females. Hypertension and diabetes were present in 74.2% and 41.2% cases respectively and both of these risk factors were found to be significantly associated with CKD. Family history of diabetes/hypertension/CKD were present in 40.2% of cases and the association was found to be significant. Conclusions: Early screening and intervention is necessary for prevention of risk factors of CKD. All patients with hypertension, diabetes, family history of CKD/hypertension/diabetes, history of chronic NSAID use should be periodically screened for CKD for its early detection and effective management.